Exceptionally large two- and three-photon absorption cross-sections by OPV organometalation12. Issue 53 (14th June 2016) - Gao, Beibei; Mazur, Leszek M.; Morshedi, Mahbod; Barlow, Adam; Wang, Huan; Quintana, Cristóbal; Zhang, Chi; Samoc, Marek; Cifuentes, Marie P.; Humphrey, Mark G.
Abstract : End-functionalization of OPVs by chlorobis{bis(diphenylphosphino)ethane}ruthenium alkynyl units affords molecules with exceptionally large two- and three-photon absorption cross-sections. Abstract : Oligo( p -phenylenevinylene)s (OPVs) containing up to 8 PV units and end-functionalized by ruthenium alkynyl groups have been prepared and their nonlinear absorption properties assessed using the Z-scan technique and employing low repetition rate femtosecond pulses. Exceptionally large two-photon absorption ( ca. 12 500 GM at 725 nm) and three-photon absorption cross sections ( ca. 1.6 × 10 −76 cm 6 s 2 at 1100 nm) are found for the 8PV-containing example, highlighting the potential of an "organometalation" approach to NLO-efficient organic materials.